NO REINO DAS ÁGUAS: ENCANTADOS, NATUREZA E CULTURA DO PANTANAL - Leite, Mário Cezar Silva (Organon, 2007)
This article stemmed from oral accounts about the Chacororé Bay, collected in field researches, in the Pantanal mato-grossense-MT, in the region of Barão de Melgaço. Through the fluency of the voice, the memory of the Pantanal communities, and of the waters, a map is obtained that goes beyond the geographical lines, the data and the natural elements. Chacororé is an enchanted bay.The Chacororé waters, in the Pantanal dwellers’ imaginary and popular culture, seem to belong and be two distinct universes at the same time. The intersectional shaping of the enchantment, between natural and supernatural, also reaches the beings and myths that live in the Chacororé. In many cases, the imaginary beings are noticed in this intersection and are given a physical materiality.